IMPLEMENTATION OF FLIPPED CLASSROOM BLOGS IN PHYSICS LEARNING FOR STUDENTS OF CLASS X SENIOR HIGH SCHOOL - Stefiana Lenisa; Muhammad Syafi’i; M. Rahmad; Yati Gusneli (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
Accommodating the latest learning challenges that require online learning support, a flipped classroom blog learning media that is valid has been produced, but has not been used in class, to see its effectiveness.Therefore the purpose of this research is to describe the cognitive learning outcomes of class X students of SMA Negeri 5 Pekanbaru, through the application of classroom flipped blog learning media on work and energy material. The research method used is Pre-Experimental desgn. The research subjects were class X students of SMA Negeri 5 Pekanbaru which numbered 36 students. Research data are online quiz data and cognitive learning outcomes from post-test scores after the use of flipped classroom blog learning media. Data were analyzed descriptively to see the level of absorption of students' cognitive learning outcomes. The results of the online quiz data analysis through the flipped classroom blog found that the overall absorption of the online quiz was 85.92% with a very good category. The results of the post-test data analysis of learning outcomes obtained an average absorptive of 81.80%, with a good average absorptive category. The effectiveness of learning based on the absorptive score of the class average includes the effective category. So that the learning media of flipped classroom blogs as innovative learning media that are effectively used in learning work and energy material in class X SMA Negeri 5 Pekanbaru.